Historical Consciousness in Forming Historical Memory - Akhmadjanov Pulatjonovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Before studying the structural structure of historical consciousness, it is important to pay attention to the levels of its formation. In scientific literature, the idea that it has four levels is more popular.